Afetividade em sala de aula: um estudo com adolescentes da rede pública de ensino - Scharpf, Luciana (2008)
The objective of this research was to investigate, from the perspective of adolescents, the feelings in the teacher-student relationship, socially vulnerable, in the public education system. Eight adolescents, four boys and four girls, all students from a public school in Campinas participated in the research. The participants studied in the same school, but in different times and grades. The focal group methodology was used. The aim was to comprehend the feelings resulting from the teacher-student relationship in the classroom, the situations that induce these feelings and how the adolescents deal with it. Thus, it is hoped, with this understanding, to contribute with the teacher s formation courses. The study pointed out the importance of the role of the educator as the person responsible for the comprehension and address of the specific needs of each age group, and sought for different strategies and methodologies of teaching to attract the curiosity of the students. By their talk, when there is commitment by the teacher, they feel seen and respected, what generates feelings of well being and a greater interest in the subject to be taught. However, the opposite is also true: there are teachers who don t worry about the specific needs of these young people, that don t engage in preparing a good class, with different dynamics and strategies, and, beyond that, they pass indifference concerning the adolescents performance and development, which causes bad feelings and reactions such as: causing troubles, leaving class, becoming angry, fighting with teachers, painting the school walls, having headaches, willing to give up studies and to fleeing from school, among others. In this analysis, the bad feelings were greatly emphasized by the students, although they also mentioned the situations which generated good feelings. This fact points the precarious relationships between teachers and students in the public education system; however, these young people still remain at school believing that the studies can offer them the means to obtain a better job